(3Hjf GdfXQjI hGdJWHjbs - (3eNJGQ(B, (3GdgGTjs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3GdNWQ hGdJCejf , GdEWGQ GdYGe ddNWQ GdJCejf chSjdI dehGLgI GdNWQ ,Gd`JCejf fTCJg hJWhQg hCfhGYg,CfhGY gjFGJ GdJCejf ,GdeHGOF GdbGfhfjI dYbO GdJCejf ,GdJCejf GdHMQj ,JCejf GdSjGQGJ ,JCejf GMLQhGdhaGI hGdTjNhNI , GdESQGa hGdQbGHI ,JCejf GdMjGI , GdCfhGY hGdCSS GdQjGVjI aj MSGH GbSGWgs
Keywords: (3GdJCejfs; (3GdNWQ hGd`JCejfs